Identification of phenazine‐1‐carboxylic acid gene (phc CD) from Bacillus pumilus MTCC7615 and its role in antagonism against Rhizoctonia solani. (23rd April 2016) - Padaria, Jasdeep Chatrath; Tarafdar, Avijit; Raipuria, Rajkumar; Lone, Showkat Ahmad; Gahlot, Pallavi; Shakil, Najam A.; Kumar, Jitendra
Abstract : Bacillus pumilus MTCC7615, a biocontrol agent isolated from rice rhizosphere was characterized to be antagonistic to Rhizoctonia solani, the pathogen causing sheath blight disease of rice. The phenazine‐1‐carboxylic acid gene ( phc CD) of this bacterium was PCR amplified (1400 bp), cloned, and sequenced. The sequence analysis revealed the presence of two ORFs of phc CD gene commonly found in Pseudomonas species . The sequence showed 98% similarity to phc CD gene of the Pseudomonas isolate LBUM223 (DQ788993). The crude antibiotic extract from B. pumilus MTCC7615 was observed to inhibit mycelial growth of R. solani under in vitro conditions. The HPLC analysis of crude antibiotic extract from B. pumilus MTCC7615 confirmed the presence of phenazine. The study has also reported the presence of phc CD gene which is responsible for the synthesis of phenazine‐1‐carboxylic acid in B. pumilus . The ability of the bacterial isolate to control sheath blight disease in rice seedlings under in vivo conditions was confirmed by the pot culture experiment. The structural and functional genomics of phc C and phc D genes would lead to a better understanding of phenazine biosynthesis in B. pumilus for its efficient utilization in plant protection strategies.